H5N1 influenza virulence, pathogenicity and transmissibility: what do we know?. (August 2015) - Neumann, Gabriele
Highly pathogenic influenza viruses of the H5N1 subtype have infected more than 600 people since 1997, resulting in the deaths of approximately 60% of those infected. Multiple studies have established the viral hemagglutinin (HA) surface glycoprotein as the major determinant of H5N1 virulence. HA mediates host-specific virus binding to cells, and mutations that allow efficient binding to viral receptors on mammalian cells are critical (although not sufficient) for H5N1 transmissibility among mammals. The viral polymerase PB2 protein is also a critical virulence determinant, and adaptive mutations in this protein are crucial for efficient H5N1 virus replication in mammals. Additionally, viral proteins (such as NS1 and PB1-F2) with roles in innate immune responses also affect the virulence of highly pathogenic H5N1 viruses.